2006
DOI: 10.1111/j.1748-1716.2006.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PLA2 isoforms by cell swelling and ischaemia/hypoxia

Abstract: Phospholipase A2 (PLA2) activity is increased in mammalian cells in response to numerous stimuli such as osmotic challenge, oxidative stress and exposure to allergens. The increased PLA2 activity is seen as an increased release of free, polyunsaturated fatty acids, e.g. arachidonic acid and membrane-bound lysophospholipids. Even though arachidonic acid acts as a second messenger in its own most mammalian cells seem to rely on oxidation of the fatty acid into highly potent second messengers via, e.g. cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 84 publications
(113 reference statements)
0
77
1
3
Order By: Relevance
“…800). Similarly, H 2 O 2 potentiates melittin-induced taurine release under isotonic conditions, yet not under hypertonic conditions (503). Thus further stimulation of arachidonic acid release by mellitin and H 2 O 2 requires that a PLA 2 is already active, which is not the case in shrunken cells.…”
Section: Plamentioning
confidence: 85%
See 2 more Smart Citations
“…800). Similarly, H 2 O 2 potentiates melittin-induced taurine release under isotonic conditions, yet not under hypertonic conditions (503). Thus further stimulation of arachidonic acid release by mellitin and H 2 O 2 requires that a PLA 2 is already active, which is not the case in shrunken cells.…”
Section: Plamentioning
confidence: 85%
“…Pharmacological evidence indicates that the swelling-induced arachidonic acid release and RVD involves cPLA 2 in EAT cells (490,989) and CHP-100 neuroblastoma cells (47), iPLA 2 and sPLA 2 in NIH3T3 cells (492,503,800), and a Ca 2ϩ -dependent PLA 2 activity in rat inner medullar collecting duct cells (996). The mechanism(s) underlying the regulation of PLA 2 activity by osmotic stress remains incompletely elucidated.…”
Section: Plamentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2ϩ -independent phospholipase A 2 (iPLA 2 -VI) hydrolyzes the sn-2 esterbond in membrane phospholipids, resulting in release of a free fatty acid and a lysophospholipid such as lysophosphatidylcholine or lysoplasmenylcholine (LPlsCho). We and others have demonstrated that iPLA 2 -VI exerts important effects on the integrity and composition of plasma membrane and organellar membranes, and in cellular signaling processes regulating cell migration, cell volume regulation, inflammation, necrosis, and programmed cell death (PCD) (26,35,42,47,48,53,60). Hypoxia/ischemia and subsequent reperfusion has been found to increase iPLA 2 -VI activity in, e.g., kidney (46), skeletal muscle (47,48), and PC12 cells (53), whereas in the heart, both activation (33,59) and inhibition (57) of iPLA 2 -VI in response to ischemiareperfusion (I/R) have been reported.…”
Section: ϩmentioning
confidence: 99%
“…In addition, it is generally assumed that living organisms respond to reduced oxygen concentrations in a cell type-and tissuespecific manner. Hypoxia also increases the release of fatty acids, including arachidonic acid (AA), in a wide variety of cell types (22,28), which participates, either directly or indirectly, in many cellular processes including the regulation of ion channels, cytokine synthesis, cell growth, eicosanoid metabolism, apoptosis, secretion, and regulation of gene expression and is also essential for neonatal growth (7,35). Although the role of signaling molecules in VEGF expression may be cell type and/or stimulus-specific, little or no information exists regarding interactions among the signaling pathways involved in proliferation of mouse embryonic stem (ES) cells under hypoxia.…”
mentioning
confidence: 99%